Realistic scenarios of pesticide exposure alters multiple biomarkers in BOANA PULCHELLA (ANURA) Adult Frogs - Pérez-Iglesias, Juan Manuel; Natale, Guillermo S.; Brodeur, Celine Marie; Larramendy, Marcelo L. (Springer, 2023)
Imazethapyr, a post-emergent herbicide used in worldwide soybean and corn crops, induces genetic and biochemical alterations in aquatic vertebrates. This study examined the relationship between biomarkers at different organization levels and imazethapyr real-life route exposure in Boana pulchella adults. Frogs were exposed to imazethapyr-based formulation Pivot® H (10.59%) at concentrations representing possible acute routes: field runoff (S1:10 mg.L−1), exposure after direct foliar application (S2:100 mg.L−1) and during direct foliar application (S3:1000 mg.L−1). Post-exposure, endpoints levels were evaluated: organism alterations, biochemical activities and cytogenetic assays. Forty-eight hours post-exposure, antioxidant enzymes decrease, micronuclei induction and DNA damage were observed in all scenarios, while cholinesterase activity increase and body condition reduction were observed in frog-exposed to S3. Ninety-six hours postexposure, frogs showed glutathione-S-transferase inhibition in S1, micronuclei induction in S2 and S3, and DNA-damage increase in S3. Herbicides routes of exposures in real-life could indicate that authorized applications have a risk to amphibian populations.